The Involvement of Pigment-Protein Fraction from Microalga Nannochloropsis oculata in Expression of Heat Shock Protein 70 with Nervous Necrosis Viral Infection on Grouper - Yanuhar, Uun; Caesar, Nico Rahman (Indonesian Journal of Natural Pigments, 2019)
The aim of this study is to investigate the expression of heat shock protein 70 (HSP70) on grouper infected by Nervous Necrosis Viral (NNV) with involvement of pigment-protein fraction (PPF) from Nannocloropsis oculata (N.oculata). Fish treatments were divided into three group, which are control, fish with PPF from N.oculata, and fish with PPF and NNV. After treatment for 23 d, fish were sacrificed, and their brain was harvested for protein analysis using SDS-Page. Fish blood was collected to examine the expression of HSP70 by hemagglutination and western blot analysis. The results showed that the expression of HSP70 was observed after treatment with PPF in NNV infected brain tissue and blood cell proved by SDS-Page and Western blot analysis. Thus, PPF is responsible for the expression of HSP70 in infected tissues, indicating that PPF appears to have a function as an inhibitor of proliferation of NNV.